2010
DOI: 10.5424/sjar/2010083-1267
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic equilibrium and physical properties evaluation affected by parchment presence of coffee grain

Abstract: Physical properties are essential for the development of silos, transport calculations, separation and classification of grain and seeds. The present work evaluates the influence of the parchment on the drying and physical properties of coffee grains. The true density (ρ t ), bulk density (ρ b ) and porosity (ε) were evaluated for coffee grains (cv. Catuaí Amarelo) with and without parchment. Four mathematical models (Chung-Pfost, GAB, Modified Henderson and Oswin) were fitted to the experimental data to acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Observed values ranged between 977 and 665 kg/m 3 for moisture contents varying between 1.127 and 0.073(decimal, d.b.). This result is in line with those presented byCorrêa et al (2010) who reported the same trend when evaluating the specific mass of coffee on parchment. In this study, the authors found that the unit-specific mass of parchment coffee reduced from 1,065 to 803 kg/m 3 during the drying process.…”
supporting
confidence: 93%
“…Observed values ranged between 977 and 665 kg/m 3 for moisture contents varying between 1.127 and 0.073(decimal, d.b.). This result is in line with those presented byCorrêa et al (2010) who reported the same trend when evaluating the specific mass of coffee on parchment. In this study, the authors found that the unit-specific mass of parchment coffee reduced from 1,065 to 803 kg/m 3 during the drying process.…”
supporting
confidence: 93%
“…The drying process reduces moisture content ( X ) and water activity ( a w ) to safe levels. High values of these two parameters may lead to the growth of microorganisms and deterioration of the product; on the other hand, low values may lead to the use of excessive energy consumed during drying and undesired alterations to the product (Corrêa et al. , 2010a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The drying process decreases the moisture content and a w of the products to a certain level (Oliveira et al, 2010). Too high moisture content and water activity may cause microorganism growth and fermentation of the product, which deteriorates the product's quality, while too low moisture content and water activity may cause excessive energy consumption and product quality damages (Correa et al, 2010; Oliveira et al, 2011). The moisture content of fresh harvested pistachio is about 45% wet basis (w.b.).…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic parameters are of importance for understanding the characteristics of water and determining the energy required for heat and mass transfer in biological systems (Dalgıç et al, 2012; Iglesias et al, 1976). To calculate the required energy, examine the features of the adsorbed water, and evaluate the food microstructure and physical events happening on its surface, understanding the thermodynamic properties of agricultural crops is crucial (Correa et al, 2010; Silva et al, 2019). Additionally, knowledge of thermodynamic properties is critical for predicting the end point at which agricultural products must be dried to obtain a product that can be stored for an extended period of time while consuming the least amount of energy possible to remove the moisture to suitable storage levels (Resende et al, 2017).…”
Section: Introductionmentioning
confidence: 99%